Physiotherapy Management for Shoulder Impingement Syndrome: A Case Report - Wanti, Qori Karunia; Sugijanto, S; Fatmarizka, Tiara (Academic Physiotherapy Conference Proceeding, 2023)
Introduction:Shoulder impingement is a symptom of pain arising from trauma, namely narrowing between the acromion and the humeral head resulting in inflammation or inflammation of the rotator cuff tendon (generally affecting the supraspinatus tendon). The typical symptom of this problem is a painful arc at 60 – 120 degrees of movement in the shoulder joint.Case Presentation:A 76 year old woman who works as a housewife complains of pain in her right shoulder. The patient has been complaining of pain since 2 years ago, the pain reappeared in November 2022 after the patient did sports activities. Examinations carried out include examination of vital signs, inspection, palpation, specific examination, examination of basic movements, measurement of pain, examination of muscle strength, measurement of joint range of motion, and measurement of functional activity.Management and Outcomes:The patient undergoes therapy at Esa Unggul Clinic Jakarta, 2 times a week. Interventions provided by physiotherapy include SWD, manual therapy, and exercise therapyConclusion:The physiotherapy program provided is in the form of SWD, manual therapy, and exercise therapy for Mrs. A was diagnosed with shoulder impingement syndrome and was treated 4 times and showed quite good results, namely decreased pain, increased range of motion, increased muscle strength, and increased functional ability.